MELAWAN ARUS (STRATEGIKOMUNITAS TOLOTANG MEMPERTAHANKAN KEPERCAYAANNYA) - Saprillah Saprillah (Balai Penelitian dan Pengembangan Agama Makassar, 2008)
This study was conducted in Amparita, Sidrap as the center ofTolotangsettlement in South Sulawesi. The study aims to describe how Tolotangcommunity maintain their identity from the dominant groups. Data wascollected using interview and observation. Interview was conductedwith community leader of Tolotang as well as Tolotang community.This study indicates that Tolotang community has a number strategy inmaintaining their identity. These strategies are integrating to Hindu,obscuring people entered into the special place, join to Golkar Party,they also strengthen their community with an exclusive marriage system,they have a strong faith. Then, this community have a good systemin maintaining their identity.